2019
DOI: 10.3390/ijerph16111898
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Misuse Among School-Going Adolescents in Thailand: Results of a National Survey in 2015

Abstract: The aim of this study was to assess the prevalence of alcohol use and misuse, and to identify its associated factors among in-school adolescents in the 2015 Thailand Global School-based Student Health Survey (GSHS). The sample included 5994 school-going adolescents (mean age 14.5 years, SD = 1.7) from Thailand that responded to the 2015 GSHS. Overall, 22.2% were current alcohol users, 24.3% had ever been drunk, 12.1% had drunk two or more alcoholic drinks in a day in the past 30 days and 10.8% had gotten into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
3
11
1
Order By: Relevance
“…The prevalence of tobacco use found in this study is consistent with the findings from earlier studies in Bangladesh [5,[28][29][30]. Although there is no study that estimated the prevalence of other substance use in Bangladesh, the prevalence reported in this study is much lower than that of other Asian [25,41] and African countries [42,43]. This difference could be due to underreporting that could be explained by two factors: strong social stigma and legal prohibition of alcohol use and other illicit drug use in Bangladesh [44].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of tobacco use found in this study is consistent with the findings from earlier studies in Bangladesh [5,[28][29][30]. Although there is no study that estimated the prevalence of other substance use in Bangladesh, the prevalence reported in this study is much lower than that of other Asian [25,41] and African countries [42,43]. This difference could be due to underreporting that could be explained by two factors: strong social stigma and legal prohibition of alcohol use and other illicit drug use in Bangladesh [44].…”
Section: Discussionsupporting
confidence: 91%
“…We report a lower overall prevalence of tobacco use (5.3%) in comparison to previous GSHS publications in Seychelles (22%) [ 52 ], Thailand (14.1%) [ 55 ], African countries (10.2%) [ 56 ], and 68 low-income and middle-income countries (13.6%) [ 57 ]. Similarly, findings from the Global Youth Tobacco Survey showed that 5.4% of South Asian adolescents were cigarette smokers [ 58 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Factors associated with alcohol use and misuse among adolescents consist of sociodemographic (male sex and older age), psychological (distress and other substance use), social problem (truancy, interpersonal violence, and injury and social support (peers and/or parents) variables (Pengpid & Peltzer, 2019). In order to better target interventions on alcohol use among adolescents, it is important to assess the current prevalence and correlates.…”
Section: Introductionmentioning
confidence: 99%